THE INFLUENCE OF SUFI TEACHINGS ON EASTERN MUSLIM CULTURE - Alimova Mukhiba Muzaffarovna (Journals Park Publishing, 2025)
This article examines the influence of Sufi teachings on the formation and development of Eastern Muslim culture. Special attention is paid to the spiritual and moral aspects of Sufism, its role in the development of literature, art, philosophy, and social thought in the Islamic East. The historical stages of the formation of Sufi orders are analyzed, and the ideas of the most prominent representatives of the Sufi tradition and their cultural heritage are explored. The study concludes that Sufism has made a significant contribution to the humanization of religious worldview and the formation of spiritual values in Muslim societies.
Keywords: Sufism, Islamic culture, spirituality, tariqa, mysticism, East, religious philosophy.